Preparation method of modified authigenic ZTA composite ceramic with good wettability with high-chromium cast iron

Modified self-generated ZTA multiphase ceramics were prepared by liquid-liquid doping, which solved the problems of poor wettability and bonding strength between ZTA ceramics and high-chromium cast iron. This method achieved uniform distribution of ceramic particles in the metal matrix and strong interfacial bonding, thereby improving the performance of the composite material.

CN121674768APending Publication Date: 2026-03-17KUNMING UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511593327.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-03
Publication Date
2026-03-17

AI Technical Summary

Technical Problem

The poor wettability and bonding strength between ZTA ceramics and high-chromium cast iron limit the application effect of ZTA ceramics in high-chromium cast iron.

Method used

Modified self-generated ZTA composite ceramics were prepared by liquid-liquid doping. A uniform ZTA/Ni precursor powder was formed by mixing a nickel precursor solution and a ZTA precursor solution, and then nickel-modified self-generated ZTA composite ceramics were formed by hot pressing and sintering.

Benefits of technology

It improves the wettability and bonding strength between ZTA ceramics and high-chromium cast iron, ensures uniform distribution of ceramic particles in the metal matrix and interfacial bonding, and enhances the performance of the composite material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121674768A_ABST
    Figure CN121674768A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of modified in-situ ZTA composite ceramic with good wettability with high-chromium cast iron, and relates to the technical field of ceramic-based composite materials. The preparation method comprises the following steps: fully stirring and mixing a ZTA precursor solution prepared from aluminum ammonium sulfate, zirconium oxychloride, yttrium nitrate, polyethylene glycol and ammonium bicarbonate through chemical coprecipitation with a Ni precursor solution prepared from nickel acetate hydrate and potassium hydroxide through a chemical precipitation method, carrying out liquid-liquid doping, and carrying out calcination and reduction processes to obtain powder; a modified authigenic ZTA multiphase ceramic block with good wettability with high-chromium cast iron can be obtained after vacuum hot pressed sintering, and the ceramic block can be used in a ceramic particle reinforced iron-based composite material after being broken and sieved; the ZTA composite ceramic is in-situ synthesis, nickel is dispersed and uniformly distributed in ZTA, an interface is improved through a wetting and diffusion mechanism, and the wettability of the ZTA and high-chromium cast iron can be effectively improved under the condition that the performance of the ZTA is not affected.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a method for preparing modified self-generated ZTA multiphase ceramics with good wettability with high-chromium cast iron, belonging to the field of ceramic matrix composite technology. Background Technology

[0002] Ceramic-reinforced metal matrix composites, possessing both the high hardness and wear resistance of ceramics and the good toughness, plasticity, and machinability of metals, have become a key focus in materials research and industrialization both domestically and internationally. Among them, zirconia-toughened alumina (ZTA) ceramics, due to their excellent wear resistance and crack resistance, are widely used in wear-resistant equipment in industries such as building materials, mining, and metallurgy. The composite of ZTA ceramic phases with metal matrices can improve the wear resistance of materials while maintaining a certain level of toughness and ductility, showing broad application prospects. High-chromium cast iron (HCCI), as a representative of third-generation wear-resistant materials, is widely used because of its excellent wear and corrosion resistance and low cost. However, with increasingly stringent operating conditions, single-metal wear-resistant materials are increasingly unable to meet requirements. Therefore, introducing ceramic phases to prepare composite materials has become the mainstream trend in wear-resistant materials, especially ZTA ceramics. However, the poor wettability and low bonding strength between ZTA and HCCI severely limit the positive effect of ZTA ceramics on the wear resistance of HCCI. Chemical modification is one of the most popular methods for surface treatment of ZTA ceramics. However, traditional ZTA chemical modification methods mostly involve solid-solid mixing of ZTA powder with metal powder, which easily leads to uneven distribution and severe agglomeration, resulting in poor modification effects on ZTA particles. Therefore, developing a preparation method that can achieve highly uniform distribution of the metal-modified phase in ZTA ceramics and form strong interfacial bonds is a technical challenge that urgently needs to be solved in this field. Summary of the Invention

[0003] To address the problems and shortcomings mentioned above, this invention provides a method for preparing a modified self-generated ZTA multiphase ceramic with good wettability with high-chromium cast iron. The modified self-generated ZTA multiphase ceramic obtained by this method exhibits good wettability with high-chromium cast iron without reducing the original properties of ZTA. This invention is achieved using the following technical solution: This invention provides a method for preparing modified self-generated ZTA multiphase ceramics with good wettability with high-chromium cast iron, comprising the following steps: (1) Preparation of nickel precursor solution: Add nickel acetate solution with pH adjusted by ammonia water dropwise to potassium hydroxide solution, and after heating and aging, a Ni precursor solution is formed; (2) Preparation of ZTA precursor solution: aluminum ammonium sulfate dodecahydrate, zirconium oxychloride octahydrate and yttrium nitrate hexahydrate are dissolved in deionized water to form salt solution ①, ammonium bicarbonate and polyethylene glycol are dissolved in deionized water to form solution ②, solution ① is added dropwise to solution ② at a uniform rate to form a mixed solution, and then the pH value of the obtained mixed solution is adjusted in a water bath and allowed to stand for aging to obtain ZTA precursor solution; (3) The nickel precursor solution and the ZTA precursor solution are mixed by liquid-liquid doping, and then filtered, washed and dried to obtain molecularly uniform ZTA / Ni precursor powder; (4) The precursor powder is reduced to obtain ZTA / Ni composite powder, and then hot-pressed and sintered to obtain the nickel-modified self-generated ZTA multiphase ceramic.

[0004] Preferably, in step (1), the molar ratio of nickel acetate to potassium hydroxide is 1:2-1:2.2, the heating temperature is 45-60℃, the pH value is 8-8.5, and the standing aging time is 3-4h.

[0005] Preferably, in step (2), the molar ratio of aluminum ammonium dodecahydrate, zirconium oxychloride octahydrate and yttrium nitrate hexahydrate is 1:0.14:0.005-1:0.2:0.01, and the molar ratio of ammonium bicarbonate and polyethylene glycol is 0.45:0.008-0.51:0.01.

[0006] Preferably, in step (2), the water bath temperature is 45-55℃, the pH value is 7.5-8.5, and the settling and aging time is 2-3h.

[0007] Preferably, the molar ratio of ZTA to Ni in the ZTA / Ni mixed powder is 0.89:0.102-0.89:0.254.

[0008] Preferably, the heating temperature in the tubular furnace is 600-800℃, and the H2 flow rate is 0.5-1.5m³. 3 / h, the time is 3-4h.

[0009] Preferably, the sintering temperature is 1100-1500℃ and the sintering time is 0.5-1h.

[0010] The present invention also claims protection for the modified self-generated ZTA / Fe multiphase ceramic prepared by the method described above, which has good wettability with high-chromium cast iron.

[0011] The beneficial effects of this invention are: (1) The modified self-generated ZTA multiphase ceramic prepared by this invention incorporates the active element Ni inside the ceramic. During sintering or molten contact, the Ni phase wets the ceramic surface, reducing the interfacial energy between the ceramic and the molten metal. Furthermore, compared with traditional solid-solid doping chemical modification of ZTA, this method uses liquid-liquid doping to uniformly mix the ZTA ceramic with the dopant element nickel, increasing the specific surface area of ​​Ni. This increases the bonding area between nickel and ZTA, thereby significantly improving interfacial wettability.

[0012] (2) Ni can react with ZTA at high temperature to generate a certain amount of transition compounds. These compounds can act as a "bridge" to combine ceramic and metal matrix. Ni is more stable and is not easily oxidized into brittle oxides. This ensures the continuity and compactness of the interface transition layer and enhances the bonding strength between ceramic particles and metal matrix.

[0013] (3) The modified self-generated ZTA composite ceramic prepared by the present invention is in-situ self-generated, which avoids the contamination between powders during solid-solid doping. Furthermore, the powder size in the composite material is all nanoscale. Therefore, the ZTA particles not only improve the original properties but also have good wettability with high-chromium cast iron, and can be directly used to prepare ceramic particle reinforced iron-based composite materials. Attached Figure Description

[0014] Figure 1 This is a SEM image of the ZTA / Ni mixed powder obtained in Example 1 of this invention; Figure 2 Here is a SEM image of the modified self-generated ZTA multiphase ceramic prepared in Example 1 of this invention; Figure 3 These are wetting angle test photos of the modified self-generated ZTA multiphase ceramic and the undoped self-generated ZTA ceramic obtained in Example 1 of this invention with high-chromium cast iron (a is the undoped self-generated ZTA ceramic, and b is the modified self-generated ZTA multiphase ceramic obtained in Example 3). Detailed Implementation

[0015] To better illustrate the purpose, technical solution, and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments. The present invention will be further described in detail below with reference to specific embodiments, but the scope of protection of the present invention is not limited thereto.

[0016] Example 1 A method for preparing modified self-generated ZTA multiphase ceramics with good wettability with high-chromium cast iron includes the following steps: (1) Ni precursor precipitate was prepared by chemical precipitation method. First, potassium hydroxide (KOH) was dissolved in deionized water and the solution temperature was kept at 45℃. Then, nickel acetate tetrahydrate [Ni(CH3COO)2·4H2O] was dissolved in deionized water and stirred thoroughly. Ammonia water was added dropwise to adjust the pH of the solution to 8. The molar ratio of nickel acetate tetrahydrate [Ni(CH3COO)2·4H2O] to potassium hydroxide (KOH) was controlled to be 1:2. After the two solutions were fully dissolved, potassium hydroxide solution was added dropwise to nickel acetate tetrahydrate solution to gradually generate light green Ni precursor precipitate.

[0017] (2) The ZTA precursor was prepared by chemical coprecipitation. First, aluminum ammonium sulfate dodecahydrate, zirconium oxychloride octahydrate and yttrium nitrate hexahydrate were dissolved in deionized water to obtain salt solution ①, and the molar ratio of the three metal salts was controlled to be 1:0.14:0.005. Then, ammonium bicarbonate and polyethylene glycol (MW (molecular weight of each ethylene glycol unit) = 44.05 g / mol, number average molecular weight Mn = 2000 g / mol) were dissolved in deionized water at a molar ratio of 0.45:0.008 to prepare solution ②. The reaction system temperature of solution ② was controlled to be 45℃ in a constant temperature water bath. Then, solution ① was added dropwise to solution ② at a uniform rate and stirred continuously for 0.5 h. Then, the pH value of the mixed solution was adjusted to 7.5 with ammonia water. Then, the resulting liquid was allowed to stand and age for 2 h to obtain the ZTA precursor solution.

[0018] (3) The nickel precursor solution obtained in step (1) is added dropwise into the ZTA precursor solution in step (2) and stirred continuously. The molar ratio of ZTA to Ni is controlled to be 0.89:0.11. After the mixture is evenly mixed, the mixed solution is filtered and washed, and then dried at 100°C for 11 hours in a drying oven to obtain a mixed powder of ZTA precursor and Ni precursor.

[0019] (4) The ZTA / Ni precursor mixed powder obtained in step (3) is placed in a tube furnace and hydrogen is introduced. The reduction furnace temperature is set to 600℃, the hydrogen flow rate is 0.5 m³ / h, and the holding time is 3h to obtain the ZTA / Ni mixed powder. Figure 1 As shown, by Figure 1 It can be seen that the self-generated ZTA / Ni mixed powder prepared by the above method has a submicron scale and uniform particle size, and the nickel dopant is evenly distributed without enrichment.

[0020] (5) The mixed powder obtained in step (4) is first pre-pressed and then placed into a graphite mold for vacuum hot pressing sintering. The designed sintering temperature is 1100℃, the sintering time is 30min, and the sintering pressure is 21MPa. After the above process, the modified self-generated ZTA multiphase ceramic can be obtained. Its microstructure is as follows: Figure 2As shown in the figure, the black area represents the alumina matrix, the gray area represents zirconium oxide, and the white area represents the nickel dopant. It can be seen from the figure that the nickel dopant is evenly distributed in the alumina matrix, with high density and no obvious defects in the composite area.

[0021] Figure 3 Finally, wetting angle test images of the modified self-generated ZTA multiphase ceramic and the undoped self-generated ZTA ceramic with high-chromium cast iron were obtained. a is the undoped self-generated ZTA ceramic, and b is the modified self-generated ZTA multiphase ceramic obtained in the last example. As can be seen from the comparison of the figures, the wetting angle of the undoped self-generated ZTA ceramic with high-chromium cast iron is about 121°, while the wetting angle of the self-generated ZTA multiphase ceramic after element doping modification is reduced to 98°. In summary, the wettability of the modified self-generated ZTA multiphase ceramic prepared in this example with the iron matrix has been improved.

[0022] Example 2 A method for preparing modified self-generated ZTA multiphase ceramics with good wettability with high-chromium cast iron includes the following steps: (1) Ni precursor precipitate was prepared by chemical precipitation method. First, potassium hydroxide (KOH) was dissolved in deionized water and the solution temperature was kept at 45℃. Then, nickel acetate tetrahydrate [Ni(CH3COO)2·4H2O] was dissolved in deionized water and stirred thoroughly. Ammonia water was added dropwise to adjust the pH of the solution to 8. The molar ratio of nickel acetate tetrahydrate [Ni(CH3COO)2·4H2O] to potassium hydroxide (KOH) was controlled to be 1:2.1. After the two solutions were fully dissolved, potassium hydroxide solution was added dropwise to nickel acetate tetrahydrate solution to gradually generate light green Ni precursor precipitate.

[0023] (2) The ZTA precursor was prepared by chemical coprecipitation. First, aluminum ammonium dodecahydrate, zirconium oxychloride octahydrate and yttrium nitrate hexahydrate were dissolved in deionized water to obtain salt solution ①, and the molar ratio of the three metal salts was controlled to be 1:0.17:0.008. Then, ammonium bicarbonate and polyethylene glycol (MW (molecular weight of each ethylene glycol unit) = 44.05 g / mol, number average molecular weight Mn = 2000 g / mol) were dissolved in deionized water at a molar ratio of 0.48:0.009 to prepare solution ②. The reaction system temperature of solution ② was controlled to be 45℃ in a constant temperature water bath. Then, solution ① was added dropwise to solution ② at a uniform rate and stirred continuously for 0.5 h. The pH value of the mixed solution was adjusted to 8 with ammonia water. The resulting liquid was then allowed to stand and age for 3 h to obtain the ZTA precursor solution.

[0024] (3) The nickel precursor solution obtained in step (1) is added dropwise into the ZTA precursor solution in step (2) and stirred continuously. The molar ratio of ZTA to Ni is controlled to be 0.89:0.17. After the mixture is evenly mixed, the mixed solution is filtered and washed, and then dried at 100°C for 12 hours in a drying oven to obtain a mixed powder of ZTA precursor and Ni precursor.

[0025] (4) The ZTA / Ni precursor mixed powder obtained in step (3) is placed in a tube furnace and hydrogen is introduced. The reduction furnace temperature is set to 750℃, the hydrogen flow rate is 1m³ / h, and the holding time is 3.5h to obtain ZTA / Ni mixed powder.

[0026] (5) The mixed powder obtained in step (4) is first pre-pressed and then placed into a graphite mold for vacuum hot pressing sintering. The designed sintering temperature is 1300℃, the sintering time is 55min, and the sintering pressure is 23MPa. After the above process, the modified self-generated ZTA multiphase ceramic can be obtained.

[0027] Example 3 A method for preparing modified self-generated ZTA multiphase ceramics with good wettability with high-chromium cast iron includes the following steps: (1) Ni precursor precipitate was prepared by chemical precipitation method. First, potassium hydroxide (KOH) was dissolved in deionized water and the solution temperature was kept at 45℃. Then, nickel acetate tetrahydrate [Ni(CH3COO)2·4H2O] was dissolved in deionized water and stirred thoroughly. Ammonia water was added dropwise to adjust the pH of the solution to 8. The molar ratio of nickel acetate tetrahydrate [Ni(CH3COO)2·4H2O] to potassium hydroxide (KOH) was controlled to be 1:2.2. After the two solutions were fully dissolved, potassium hydroxide solution was added dropwise to nickel acetate tetrahydrate solution to gradually generate light green Ni precursor precipitate.

[0028] (2) The ZTA precursor was prepared by chemical coprecipitation. First, aluminum ammonium sulfate dodecahydrate, zirconium oxychloride octahydrate and yttrium nitrate hexahydrate were dissolved in deionized water to obtain salt solution ①, and the molar ratio of the three metal salts was controlled to be 1:0.2:0.01. Then, ammonium bicarbonate and polyethylene glycol (MW (molecular weight of each ethylene glycol unit) = 44.05 g / mol, number average molecular weight Mn = 2000 g / mol) were dissolved in deionized water at a molar ratio of 0.51:0.01 to prepare solution ②. The reaction system temperature of solution ② was controlled to be 45℃ in a constant temperature water bath. Then, solution ① was added dropwise to solution ② at a uniform rate and stirred continuously for 0.5 h. Then, the pH value of the mixed solution was adjusted to 8 with ammonia water. Then, the resulting liquid was allowed to stand and age for 3.5 h to obtain the ZTA precursor solution.

[0029] (3) The nickel precursor solution obtained in step (1) is added dropwise into the ZTA precursor solution in step (2) and stirred continuously. The molar ratio of ZTA to Ni is controlled to be 0.89:0.25. After the mixture is evenly mixed, the mixed solution is filtered and washed, and then dried at 100°C for 13 hours in a drying oven to obtain a mixed powder of ZTA precursor and Ni precursor.

[0030] (4) The ZTA / Ni precursor mixed powder obtained in step (3) is placed in a tube furnace and hydrogen is introduced. The reduction furnace temperature is set to 800℃, the hydrogen flow rate is 1.5m³ / h, and the holding time is 4h to obtain ZTA / Ni mixed powder.

[0031] (5) The mixed powder obtained in step (4) is first pre-pressed and then placed into a graphite mold for vacuum hot pressing sintering. The designed sintering temperature is 1500℃, the sintering time is 1h, and the sintering pressure is 25MPa. After the above process, the modified self-generated ZTA multiphase ceramic can be obtained.

[0032] Comparative Example 1 A method for preparing modified self-generated ZTA multiphase ceramics with good wettability with high-chromium cast iron includes the following steps: (1) Ni precursor precipitate was prepared by chemical precipitation method. First, potassium hydroxide (KOH) was dissolved in deionized water and the solution temperature was kept at 45℃. Then, nickel acetate tetrahydrate [Ni(CH3COO)2·4H2O] was dissolved in deionized water and stirred thoroughly. Ammonia water was added dropwise to adjust the pH of the solution to 8. The molar ratio of nickel acetate tetrahydrate [Ni(CH3COO)2·4H2O] to potassium hydroxide (KOH) was controlled to be 1:2. After the two solutions were fully dissolved, potassium hydroxide solution was added dropwise to nickel acetate tetrahydrate solution to gradually generate light green Ni precursor precipitate.

[0033] (2) The ZTA precursor was prepared by chemical coprecipitation. First, aluminum ammonium sulfate dodecahydrate, zirconium oxychloride octahydrate and yttrium nitrate hexahydrate were dissolved in deionized water to obtain salt solution ①, and the molar ratio of the three metal salts was controlled to be 1:0.14:0.005. Then, ammonium bicarbonate and polyethylene glycol (MW (molecular weight of each ethylene glycol unit) = 44.05 g / mol, number average molecular weight Mn = 2000 g / mol) were dissolved in deionized water at a molar ratio of 0.45:0.008 to prepare solution ②. The reaction system temperature of solution ② was controlled to be 45℃ in a constant temperature water bath. Then, solution ① was added dropwise to solution ② at a uniform rate and stirred continuously for 0.5 h. Then, the pH value of the mixed solution was adjusted to 7.5 with ammonia water. Then, the resulting liquid was allowed to stand and age for 2 h to obtain the ZTA precursor solution.

[0034] (3) The nickel precursor solution obtained in step (1) is added dropwise into the ZTA precursor solution in step (2) and stirred continuously. The molar ratio of ZTA to Ni is controlled to be 0.89:0.11. After the mixture is evenly mixed, the mixed solution is filtered and washed, and then dried at 100°C for 11 hours in a drying oven to obtain a mixed powder of ZTA precursor and Ni precursor.

[0035] (4) The ZTA / Ni precursor mixed powder obtained in step (3) is placed in a tube furnace and hydrogen is introduced. The reduction furnace temperature is set to 600℃, the hydrogen flow rate is 0.5 m³ / h, and the holding time is 3h to obtain ZTA / Ni mixed powder.

[0036] (5) The mixed powder obtained in step (4) is first pre-pressed and then placed into a graphite mold for vacuum hot pressing sintering. The designed sintering temperature is 1100℃, the sintering time is 30min, and the sintering pressure is 21MPa. After the above process, the modified self-generated ZTA multiphase ceramic can be obtained.

[0037] The modified self-generated ZTA multiphase ceramic prepared in this comparative example has a hardness of 20.35 GPa, a density of 95%, and a wetting angle of 104.2° with high-chromium cast iron. The comparison shows that the addition of nickel does not change the original properties of ZTA and even reduces the wetting angle to some extent. This is because the uniform distribution of nickel acts as a lubricant for the ZTA.

[0038] Comparative Example 2 A method for preparing modified self-generated ZTA multiphase ceramics with good wettability with high-chromium cast iron includes the following steps: (1) Ni precursor precipitate was prepared by chemical precipitation method. First, potassium hydroxide (KOH) was dissolved in deionized water and the solution temperature was kept at 45℃. Then, nickel acetate tetrahydrate [Ni(CH3COO)2·4H2O] was dissolved in deionized water and stirred thoroughly. Ammonia water was added dropwise to adjust the pH of the solution to 8. The molar ratio of nickel acetate tetrahydrate [Ni(CH3COO)2·4H2O] to potassium hydroxide (KOH) was controlled to be 1:2.1. After the two solutions were fully dissolved, potassium hydroxide solution was added dropwise to nickel acetate tetrahydrate solution to gradually generate light green Ni precursor precipitate.

[0039] (2) The ZTA precursor was prepared by chemical coprecipitation. First, aluminum ammonium dodecahydrate, zirconium oxychloride octahydrate and yttrium nitrate hexahydrate were dissolved in deionized water to obtain salt solution ①, and the molar ratio of the three metal salts was controlled to be 1:0.17:0.008. Then, ammonium bicarbonate and polyethylene glycol (MW (molecular weight of each ethylene glycol unit) = 44.05 g / mol, number average molecular weight Mn = 2000 g / mol) were dissolved in deionized water at a molar ratio of 0.48:0.009 to prepare solution ②. The reaction system temperature of solution ② was controlled to be 45℃ in a constant temperature water bath. Then, solution ① was added dropwise to solution ② at a uniform rate and stirred continuously for 0.5 h. The pH value of the mixed solution was adjusted to 8 with ammonia water. The resulting liquid was then allowed to stand and age for 3 h to obtain the ZTA precursor solution.

[0040] (3) The nickel precursor solution obtained in step (1) is added dropwise into the ZTA precursor solution in step (2) and stirred continuously. The molar ratio of ZTA to Ni is controlled to be 0.89:0.17. After the mixture is evenly mixed, the mixed solution is filtered and washed, and then dried at 100°C for 12 hours in a drying oven to obtain a mixed powder of ZTA precursor and Ni precursor.

[0041] (4) The ZTA / Ni precursor mixed powder obtained in step (3) is placed in a tube furnace and hydrogen is introduced. The reduction furnace temperature is set to 750℃, the hydrogen flow rate is 1m³ / h, and the holding time is 3.5h to obtain ZTA / Ni mixed powder.

[0042] (5) The mixed powder obtained in step (4) is first pre-pressed and then placed into a graphite mold for vacuum hot pressing sintering. The designed sintering temperature is 1300℃, the sintering time is 55min, and the sintering pressure is 23MPa. After the above process, the modified self-generated ZTA multiphase ceramic can be obtained.

[0043] The modified self-generated ZTA multiphase ceramic prepared in this comparative example has a hardness of 22.38 GPa, a density of 97%, and a wetting angle of 101.9° with high-chromium cast iron. The comparison shows that a small increase in nickel content actually improves the mechanical properties of ZTA, and the decrease in the wetting angle with high-chromium cast iron is more significant. This is because the uniform distribution of nickel in ZTA refines the grains, thus improving the mechanical properties of ZTA. Furthermore, the modification effect of nickel is amplified with increasing nickel content.

[0044] Comparative Example 3 A method for preparing modified self-generated ZTA multiphase ceramics with good wettability with high-chromium cast iron includes the following steps: (1) Ni precursor precipitate was prepared by chemical precipitation method. First, potassium hydroxide (KOH) was dissolved in deionized water and the solution temperature was kept at 45℃. Then, nickel acetate tetrahydrate [Ni(CH3COO)2·4H2O] was dissolved in deionized water and stirred thoroughly. Ammonia water was added dropwise to adjust the pH of the solution to 8. The molar ratio of nickel acetate tetrahydrate [Ni(CH3COO)2·4H2O] to potassium hydroxide (KOH) was controlled to be 1:2.2. After the two solutions were fully dissolved, potassium hydroxide solution was added dropwise to nickel acetate tetrahydrate solution to gradually generate light green Ni precursor precipitate.

[0045] (2) The ZTA precursor was prepared by chemical coprecipitation. First, aluminum ammonium sulfate dodecahydrate, zirconium oxychloride octahydrate and yttrium nitrate hexahydrate were dissolved in deionized water to obtain salt solution ①, and the molar ratio of the three metal salts was controlled to be 1:0.2:0.01. Then, ammonium bicarbonate and polyethylene glycol (MW (molecular weight of each ethylene glycol unit) = 44.05 g / mol, number average molecular weight Mn = 2000 g / mol) were dissolved in deionized water at a molar ratio of 0.51:0.01 to prepare solution ②. The reaction system temperature of solution ② was controlled to be 45℃ in a constant temperature water bath. Then, solution ① was added dropwise to solution ② at a uniform rate and stirred continuously for 0.5 h. Then, the pH value of the mixed solution was adjusted to 8 with ammonia water. Then, the resulting liquid was allowed to stand and age for 3.5 h to obtain the ZTA precursor solution.

[0046] (3) The nickel precursor solution obtained in step (1) is added dropwise into the ZTA precursor solution in step (2) and stirred continuously. The molar ratio of ZTA to Ni is controlled to be 0.89:0.25. After the mixture is evenly mixed, the mixed solution is filtered and washed, and then dried at 100°C for 13 hours in a drying oven to obtain a mixed powder of ZTA precursor and Ni precursor.

[0047] (4) The ZTA / Ni precursor mixed powder obtained in step (3) is placed in a tube furnace and hydrogen is introduced. The reduction furnace temperature is set to 800℃, the hydrogen flow rate is 1.5m3 / h, and the holding time is 4h to obtain ZTA / Ni mixed powder.

[0048] (5) The mixed powder obtained in step (4) is first pre-pressed and then placed into a graphite mold for vacuum hot pressing sintering. The designed sintering temperature is 1500℃, the sintering time is 1h, and the sintering pressure is 25MPa. After the above process, the modified self-generated ZTA multiphase ceramic can be obtained.

[0049] The modified self-generated ZTA multiphase ceramic prepared in this comparative example has a hardness of 18.5 GPa, a density of 93%, and a wetting angle of 98° with high-chromium cast iron. The comparison shows that exceeding a certain nickel content actually reduces the mechanical properties of ZTA, but the decrease in the wetting angle between ZTA and high-chromium cast iron is more significant. This is because nickel is a soft phase, and a high nickel content will actually reduce the mechanical properties of ZTA.

[0050] Finally, it should be noted that the above preferred embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail through the above preferred embodiments, those skilled in the art should understand that various changes can be made to it in form and detail without departing from the scope defined by the claims of the present invention.

Claims

1. A method for producing a modified autogenous ZTA composite ceramic having good wettability with high chromium cast iron, characterized in that, The method comprises the following steps: (1) preparing a nickel precursor solution: adding a nickel acetate solution with pH value adjusted by ammonia water into a potassium hydroxide solution drop by drop, and forming a Ni precursor solution after heating and aging; (2) preparing a ZTA precursor solution: dissolving aluminum ammonium sulfate dodecahydrate, zirconium oxychloride octahydrate and yttrium nitrate hexahydrate in deionized water to form a salt solution 1, dissolving ammonium bicarbonate and polyethylene glycol in deionized water to form a solution 2, adding the solution 1 into the solution 2 at a constant speed to form a mixed solution, and then adjusting the pH value of the mixed solution in a water bath and standing to obtain the ZTA precursor solution after aging; (3) adding the Ni precursor solution into the ZTA precursor solution, and obtaining a molecularly uniform ZTA / Ni precursor powder after filtration, washing and drying; (4) reducing the precursor powder to obtain a ZTA / Ni composite powder, and then performing hot-pressing sintering to obtain the nickel-modified autogenous ZTA composite ceramic.

2. The method of claim 1, wherein, The nickel precursor in step (1) is Ni(OH)2, and the ZTA precursor in step (2) is a co-precipitate of carbonates or hydroxides of Al, Zr and Y.

3. The method for preparing modified autogenous ZTA composite ceramic with good wettability to high chromium cast iron according to claim 1, characterized in that: In step (1), the pH value of the nickel acetate is 8-8.5, the molar ratio of the nickel acetate to the potassium hydroxide is 1:2-1:2.2, the heating temperature is 45-60℃, and the standing aging time is 3-4h.

4. The method for preparing modified autogenous ZTA composite ceramic with good wettability to high chromium cast iron according to claim 1, characterized in that: In step (2), the molar ratio of the aluminum ammonium sulfate dodecahydrate, the zirconium oxychloride octahydrate and the yttrium nitrate hexahydrate is 1:0.14:0.005-1:0.2:0.01, and the molar ratio of the ammonium bicarbonate to the polyethylene glycol is 0.45:0.008-0.51:0.

01.

5. The method for preparing modified autogenous ZTA composite ceramic with good wettability to high chromium cast iron according to claim 1, characterized in that: In step (2), the temperature of the water bath is 45-55℃, the pH value is 7.5-8.5, and the standing aging time is 2-3h.

6. The method for preparing modified autogenous ZTA composite ceramic with good wettability to high chromium cast iron according to claim 1, characterized in that: In step (3), the molar ratio of ZTA to Ni in the ZTA / Ni mixed powder is 0.89:0.102-0.89:0.

254.

7. The method of claim 1, wherein, In step (3), the liquid-liquid doping mixing refers to physically mixing two or more precursor solutions uniformly distributed in liquid state to realize atomic / molecular level uniform distribution of components.

8. The method for preparing modified autogenous ZTA composite ceramic with good wettability to high chromium cast iron according to claim 1, characterized in that: Step (4) is heating in a tube furnace at a temperature of 600-800 °C, H2flow rate of 0.5-1.5 m 3 / h, time of 3-4 h.

9. The method for preparing modified autogenous ZTA composite ceramic with good wettability to high chromium cast iron according to claim 1, characterized in that: In step (4), the sintering temperature is 1100-1500℃, and the time is 0.5-1h.